(untitled) (Update Dental College Journal, 2017)
Musculoskeletal disorders (MSDs) represent a significant occupational problem among health care professionals; however, data on prevalence of work-related musculoskeletal disorders (WMSDs) are limited in our country for referencing. A descriptive cross sectional study was conducted during January to December 2016 among 160 health care professionals (doctors, nurses) working in a tertiary care hospital in Dhaka city. The aim of the study was to determine the prevalence, distribution and to find out the multiple risk factors that contribute to the development of WMSDs among the sample population. Data were collected with semi structured questionnaire based on a validated research instrument Standardized Nordic Questionnaire (SNQ) which records the prevalence of MSDs in terms of musculoskeletal symptoms (ache, pain, discomfort) in the preceding 12 months. The statistical analysis was done by using the SPSS software 21 version. The study result revealed that out of 160 (100.0%) health care professionals 109 (68.1%) had musculoskeletal pain or discomfort in the last 12 months and 51 (31.9%) had not, and it was also found that 57 (61.3%) doctors and 52 (77.6%) nurses had musculoskeletal pain or discomfort in the last 12 months and the prevalence of work-related musculoskeletal disorders in different body region in the last 12 months, where more than 1 site involvement 46 (42.2%) followed by neck 19 (17.4%), shoulder 15 (13.8%), lower back 13 (11.9%), hips 8 (7.3%), hand/fingers 5 (4.6%). About the self reported risk factors among the health care professionals for WMSDs were found working the same position for long periods 48 (29.8%),followed by treating excessive number of patients in a day 47 (29.1%), inadequate training on injury prevention 25 (15.9%), working awkward or cramped position18(11.6%).There were no statistically significant association found in age and years of experience of the health care professionals with the WMSDs (p value .281, .083 respectively), but significant association found in sex and occupation of the health care professionals with WMSDs (p value .045, .031 respectively). As because a high proportion of health care professionals had WMSDs and they are on the risk for development of WMSDs, it can be recommended that education programmes on prevention and coping strategies for musculoskeletal disorders be made mandatory for health care professionals in order to reduce the rate of WMSDs among them and to promote efficiency in patient care. Update Dent. Coll. j: 2017; 7 (1): 04-09